Pemberontakan Gandor 1895: Sebuah Perlawanan Kaum Sufi Terhadap Kekuasaan - Abd. Salam (Universitas Islam Negeri Mataram, 2005)
The settling Dutch colonial power in Lombok took strong effect on the whole life aspects of the people of the island. Any policies implemented by the colonial always resulted in restlessness among people. Economics policy throttled people’s life, and politics policy even abused their religious sentiment especially Muslims that was the majority people. These two unfair policies resulted in hate among people and in turn flamed people struggle against Dutch. This was the background of Gandor struggle in 1895. This article is aimed at revealing and describing factors forming the background of Gandor struggle, and then its process and results. The struggle was actually caused and supported by many factors, and the religious doctrines and leadership were the most significant ones that flamed the heroic spirit of the people. Through social and historical approach this article uncovers and elaborates historical facts relating to the struggle.